The Impact of Knowledge Management and Entrepreneur’s Knowledge on Innovation and Firm Performance - Hartono, Hendry; Halim, Erwin (Journal the Winners: Economics, Business, Management, and Information System Journal, 2014)
There is lack of evidence from previous studies that examined the relationships among entrepreneur’s knowledge, knowledge management, innovation, and firm performance. Entrepreneur if s/he has more knowledge than other entrepreneurs can be more competitive. Literature studies show that entrepreneur knowledge and knowledge management had significant and direct positive effect on innovation and firm performance. Further studies are needed for showing a model and factors that enhance innovation and improve firm performance. The purpose of this paper is to propose a framework of improving the firm performance by enhancing of the innovation, through the entrepreneur knowledge and knowledge management. Based on this paper, further research is needed on the potential role of EK and KM in innovation, and how the value of EK and KM can be maximized to have a more valuable innovation that would be an impact on firm performance.